2016
DOI: 10.3390/agronomy6030039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Formulation on the Cuticular Penetration and on Spray Deposit Properties of Manganese and Zinc Foliar Fertilizers

Abstract: Foliar fertilization, or the application of nutrient solutions to the foliage of plants, has become a very important tool as a supplement to traditional soil fertilization. So far, knowledge about the real mechanisms of foliar nutrient uptake is still limited. In this study different manganese (Mn) and zinc (Zn) carriers differing in their solubility and chemical characteristics (chelated or non-chelated, with or without the presence of a surfactant-penetrant) were compared with regard to their penetration cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
3
14
0
1
Order By: Relevance
“…These findings indicate that nano-ZnO was likely absorbed in the same form as ZnSO4 -soluble Zn ions rather than as intact ZnO particles. This is in agreement with previous studies, including a similar studies of Li et al (2018) in soybean and Alexander et al (2016) found that absorption of insoluble foliar applied nutrients was limited (even for nano-scale particles). Therefore, solubility is an important factor to consider when designing foliar fertilisers.…”
Section: Comparing the Absorption Of Nano-zno And Znso4supporting
confidence: 94%
“…These findings indicate that nano-ZnO was likely absorbed in the same form as ZnSO4 -soluble Zn ions rather than as intact ZnO particles. This is in agreement with previous studies, including a similar studies of Li et al (2018) in soybean and Alexander et al (2016) found that absorption of insoluble foliar applied nutrients was limited (even for nano-scale particles). Therefore, solubility is an important factor to consider when designing foliar fertilisers.…”
Section: Comparing the Absorption Of Nano-zno And Znso4supporting
confidence: 94%
“…In this study, the effect of nano( Fe, Cu, Zn and Mn) was determined by single and combination on the growth and yield of Jerusalem artichoke To our knowledge this is the first report showing that the spraying of nano-fertilizers of micro-elements has affected the improvement of the growth and yield of Jerusalem artichoke and the same response was obtained in other types of crops that have different requirements for micro-nutrients. There are still many unanswered questions about how the effects of micronutrients are affected by the increase in the yield and its components, and( Fe, Cu, Zn and Mn) content in leaves and tubers of the Jerusalem artichoke, One possibility is that micronutrient foliar QJAS Al-Qadisiyah Journal For Agriculture Sciences ISSN: 2618-1479 Volume 9, No.1 ,(2019), PP 156-164 http://qu.edu.iq/jouagr/index.php/QJAS/index Page 162 | http://qu.edu.iq/jouagr/index.php/QJAS/index nutrition can affect the accumulation of dry matter in arial parts and increase the percentage of dry matter in tubers [18], [27].…”
Section: Resultsmentioning
confidence: 99%
“…During the plant phonological stages vulnerable to drought effects, moisture stress occurs in various forms such as; pre-flowering water deficit (regions of South America); grain-filling (post-anthesis) water deficit (Mediterranean regions) and continuous water deficit [14]. Foliar fertilization has progressed over time, following many decades of research and development, an indispensable tool for the sustainable agricultural approach and is of supreme commercial importance internationally [15,16]. In addition to achieving more practical experience regarding the optimum stages of foliar fertilizer application, little is known about the possibilities of improving foliar nutrient penetration into leaf or fruit tissues [16].…”
Section: Introductionmentioning
confidence: 99%
“…Foliar fertilization has progressed over time, following many decades of research and development, an indispensable tool for the sustainable agricultural approach and is of supreme commercial importance internationally [15,16]. In addition to achieving more practical experience regarding the optimum stages of foliar fertilizer application, little is known about the possibilities of improving foliar nutrient penetration into leaf or fruit tissues [16]. In many orchards, macronutrients and especially micronutrients are leaf-applied routinely to prevent the deficiencies of these essential elements [17].…”
Section: Introductionmentioning
confidence: 99%